In July 2019 the Portuguese Society of Myology was officially born: the first message from the founders - Paula Tavares; Carlos Fontes Ribeiro (PAGEPress Publications, 2019)
The amazing behaviour and adaptation capacity of the skeletal muscle system call the attention of several scientists, including us. Thus, we have the pleasure to announce that it was born in the city of Coimbra, Portugal, the Portuguese Society of Myology (SPMyo), a society which the main aim is to spread skeletal muscle knowledge in the areas of muscle physiology, physiopathology and pharmacology in a multidisciplinary organization that reflects the different areas of the skeletal muscle study. The commitment of SPMyo is the progress of skeletal muscle awareness as well as its investigation, encouraging interdisciplinary, national and international collaboration. These goals will be achieved by organization of scientific meetings, formation courses, publications of books and other scientific and didactic materials. It is also a goal of the SPMyo to organize public events allowing general public to understand skeletal muscle system.